Achievements and challenges in psychiatric education and training in Sri Lanka - Hapangama, Aruni; Kuruppuarachchi, K.A.L.A.; Hanwella, Raveen (Cambridge University Press, 2021)
When compared with other Asian countries, psychiatric education and training in Sri Lanka has made significant developments during the past two decades, such as introducing psychiatry as a separate final year subject in the undergraduate medical curricula. However, further developments in psychiatric training in medical education are needed.
Keywords: South Asia; challenges; internship; undergraduate curriculum; MEDICINE::Psychiatry